1992
DOI: 10.1073/pnas.89.12.5256
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal gene clusters are uniquely proportioned between open and closed chromatin structures in both tomato leaf cells and exponentially growing suspension cultures.

Abstract: The accessibility of regulatory molecules to specific DNA sequences and chromatin regions in the nucleus is crucial to gene expression. In this study, we examined the chromatin structure in tomato leaf cells and in exponentially growing tomato cell suspension cultures. The structure of ribosomal chromatin was investigated by micrococcal nuclease and psoralen photocrosslinking. We showed that ribosomal genes in tomato are folded into two While the structure of inactive bulk chromatin is fairly well understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 30 publications
(38 reference statements)
1
21
0
Order By: Relevance
“…2 to 4). The most sensitive assay for detecting the level of active rDNA units is psoralen cross-linking (13,15,16,47). However, our psoralen crosslinking study did not reveal active units, suggesting such units represent less than 10% of the units in any of the bands we detected on Southern blots (Fig.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…2 to 4). The most sensitive assay for detecting the level of active rDNA units is psoralen cross-linking (13,15,16,47). However, our psoralen crosslinking study did not reveal active units, suggesting such units represent less than 10% of the units in any of the bands we detected on Southern blots (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Sogo and colleagues have demonstrated that transcriptionally active rDNA units are more accessible to psoralen and after UV cross-linking can be separated from the inactive units by their slower migration during electrophoresis (14). This psoralen accessibility has been used to detect active rDNA units in many organisms (13,15,16,47). Isolated nuclei from 1-16-h embryos were incubated with psoralen and UV crosslinked (15,47,58).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Data are the mean Ϯ 1 SD of three independent experiments. bracket) correspond to incomplete digestion of some rDNA sequences, because of the presence of psoralen crosslinks close to the restriction sites (27,38).…”
Section: Resultsmentioning
confidence: 99%
“…The ribosomal genes are present in multiple copies (ϳ150 in yeast) that are organized in long tandem repeats (55). In most organisms only a portion of rDNA is transcriptionally active (reviewed in references 20 and 32), and the fraction of active rDNA varies markedly among organisms and cell types (e.g., from ϳ20% to ϳ70%) (8)(9)(10)(11). Furthermore, in yeast, the active rDNA population varies according to growth rate, with the highest proportion of active genes (about 50%) present in exponentially growing cells (10,13).…”
mentioning
confidence: 99%